Optimization of an off-shore wind farm collection grid - Malz, Elena (My University, 2012)
Offshore wind energy has aroused interest in the previous years and the wind power industry is growing constantly. The investment for a wind farm is enormous and therefore maximal revenue is required by reducing any kind of losses. However, since the offshore wind energy technology is still in an early state, there is a lack of an optimal grid design. In this thesis the relationship between reliability and financial losses is studied. It is obvious that the more reliability a wind farm shows, the more a secure power production can be expected. However, there is an upper limit, where adding more reliability implies increasing investment costs without adding more benefit. For an investigation of this limit, a ring layout is chosen, which connects eight 6 MW wind turbines. Six layouts with different reliabilities are considered, from a radial layout up to a full redundancy solution. By calculating power losses and the corresponding losses in revenues, the effect of the in uence parameters, wind speed and electricity price is studied. Finally a comparison between the layouts is done, which results in a minimum of financial losses at a redundancy around 70-75%.
Keywords: Elkraftteknik; Electric power engineering